Concomitant or late aortic valve intervention and its efficacy for aortic insufficiency associated with continuous-flow left ventricular assist device implantation - Ando, Masahiko; Ono, Minoru (Frontiers in Cardiovascular Medicine, 2022)
Moderate to severe aortic insufficiency (AI) in patients who underwent continuous-flow left ventricular assist device (CF-LVAD) implantation is a significant complication. According to the INTERMACS registry analysis, at least mild AI occurs in 55% of patients at 6 months after CF-LVAD implantation and moderate to severe AI is significantly associated with higher rates of re-hospitalization and mortality. The clinical implications of these data may underscore consideration of prophylactic aortic valve replacement, or repair, at the time of CF-LVAD implantation, particularly with expected longer duration of support and in patients with preexisting AI that is more than mild. More crucially, even if a native aortic valve is seemingly competent at the time of VAD implantation, we frequently find de novo AI as time goes by, potentially due to commissural fusion in the setting of inconsistent aortic valve opening or persistent valve closure caused by CF-LVAD support, that alters morphological and functional properties of innately competent aortic valves. Therefore, close monitoring of AI is mandatory, as the prognostic nature of its longitudinal progression is still unclear. Clearly, significant AI during VAD support warrants surgical intervention at the appropriate timing, especially in patients of destination therapy. Nonetheless, such an uncertainty in the progression of AI translates to a lack of consensus regarding the management of this untoward complication. In practice, proposed surgical options are aortic valve replacement, repair, closure, and more recently transcatheter aortic valve implantation or closure. Transcatheter approach is of course less invasive, however, its efficacy in terms of long-term outcome is limited. In this review, we summarize the recent evidence related to the pathophysiology and surgical treatment of AI associated with CF-LVAD implantation.